2019
DOI: 10.1371/journal.pone.0214413
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of leptin are associated with severity parameters in visceral leishmaniasis patients

Abstract: Visceral leishmaniasis (VL) is the most severe clinical form of leishmaniasis, and if untreated may be fatal. It affects important organs of the immune system and is characterized by a specific immunosuppression, along with intense cellular activation and cytokine storm. Moreover, VL is now recognized as a systemic inflammatory response syndrome (SIRS), in which multiple cytokines and other pro-inflammatory molecules are released. The action of these inflammatory mediators may be considered risk factors for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Alternatively, ob/ob mice showed higher liver parasite burden when comparing with infected wild-type mice. Moreover, an impaired leptin signaling is linked to a reduction of the innate immune response to Leishmania [ 253 ], and low levels of leptin have been associated with severity parameters in visceral leishmaniasis patients [ 254 ]. Additionally, Trypanosoma cruzi , the etiological agent of Chagas´ disease, also causes an intense inflammatory response within the liver.…”
Section: Leptin and Other Liver Pathologiesmentioning
confidence: 99%
“…Alternatively, ob/ob mice showed higher liver parasite burden when comparing with infected wild-type mice. Moreover, an impaired leptin signaling is linked to a reduction of the innate immune response to Leishmania [ 253 ], and low levels of leptin have been associated with severity parameters in visceral leishmaniasis patients [ 254 ]. Additionally, Trypanosoma cruzi , the etiological agent of Chagas´ disease, also causes an intense inflammatory response within the liver.…”
Section: Leptin and Other Liver Pathologiesmentioning
confidence: 99%
“…Finally, we observed that IL-6, a cytokine known to be in ammatory and already associated with a more severe prognosis in the evolution of VL [12,17], was correlated to laboratory severity markers, such as hypoalbuminemia, leukopenia and thrombocytopenia. As expected, C-reactive protein (CRP) levels also correlated positively with IL-6 since its binding with its receptor activates immunocompetent and hematological cells leading to the production of acute phase responses, as CRP [59].…”
Section: Discussionmentioning
confidence: 66%
“…In parallel, the levels of speci c anti-Leishmania IgG and their subclasses after active VL may have an important role as marker of cure and/or predisposition to relapse [17,53]. Here, IgG3 levels are persistently increased in R-VL group in relation to NR-VL, which may show the presence of continuous parasite stimulation, without a complete control by the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allied to this, elevated levels of lipopolysaccharide (LPS) pointed out that microbial products from the gut lumen translocation, could also be involved in the exacerbated pro-inflammatory status of VL alone (6) and VL/HIV co-infected patients (2,7). Plasma inflammatory cytokines levels, as well as soluble molecules associated with inflammation such as d-dimers, neopterin, soluble CD163 and leptin levels have been described as important predictors of severity and death in VL (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%